Galectins‐1, ‐3, ‐7, ‐8 and ‐9 as prognostic markers for survival in epithelial ovarian cancer: A systematic review and meta‐analysis. Issue 3 (25th December 2020) - Pergialiotis, Vasilios; Papoutsi, Eleni; Androutsou, Anastasia; Tzortzis, Andrianos‐Serafeim; Frountzas, Maximos; Papapanagiotou, Angeliki; Kontzoglou, Konstantinos
Abstract: Background: Galectins are a family of proteins that have recently emerged as regulators of cancer biology. Objectives: To investigate the impact of peritumoral and tumoral galectin expression on ovarian cancer prognosis. Search strategy: We searched Medline, Cochrane, and EMBASE databases from inception until March 22, 2020. Selection criteria: All studies correlating galectins and ovarian cancer prognosis were selected. Data collection and analysis: The literature search presented 11 studies, which contained 1034 patients. Meta‐analysis was performed with RevMan 5.3 software. Main results: Studies were stratified into two groups depending on the location of galectin expression (peritumoral stroma or nucleus/cytoplasm of tumor cells). Tumoral galectin‐7 and galectin‐9 expression was significantly associated with poor overall survival (odds ratio [OR] 2.06, 95% confidence interval [CI] 1.32–3.21, P  = 0.001; OR 1.71, 95% CI 1.27–2.30, P  < 0.001, respectively). The total effect of high tumoral expression of galectins in overall survival and progression‐free survival was significant (OR 1.51, 95% CI 1.02–2.23, P  = 0.04; OR 2.76, 95% CI 1.73–4.40, P  < 0.001, respectively). Conclusions: Our results suggest that galectins are implicated in ovarian cancer prognosis; however, further research is needed to ascertain their actual importance as well as their diagnostic accuracy. Synopsis: Overall, our study highlights that tumoral (cytoplasmic or nuclear) galectin‐7, ‐9 expression negatively affects overall survival among patients with ovarian cancer.